Perkembangan Pandangan Gereja Katolik terhadap Ilmu Pengetahuan - ‘Ulum, Mukhottotun; HS, Moh. Nuh (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
Science and the Church are often viewed as being in opposition to one another. This perspective frequently led to conflict, as science and religion were considered to originate from different realms. However, the intellectual developments of this period, along with contributions from figures such as Galileo and Newton, began to explore the domain of science. These scientists examined nature, methods in theology, the relationship between God and the universe, and human interaction with the natural world. The Catholic Church sought to maintain the purity of its teachings through the Inquisition, an institution tasked with monitoring and prosecuting those who propagated heretical doctrines. Throughout the history of Western civilization, theological debates have often posed significant challenges. During this time, reason and philosophy were not employed to challenge religious doctrines but rather to clarify them. Scholars like Saint Anselm, Abelard, and Thomas Aquinas endeavored to integrate reason with the revelation of the Bible. Their approach reflects an effort to find harmony between logical reasoning and religious faith.